Congenital Colon Arteriovenous Malformation Misdiagnose in a 25-Year-Old Woman - Saeed Derakhshani (Shiraz University of Medical Sciences, 2014)
Background Anastomotic leakage is claimed to be responsible for about one third of deaths following colon surgeries. Therefore, research on applied materials that may prevent leakage and improve healing requires more attention. Objectives This study was conducted to determine surgical and histological outcomes of applying human amniotic membrane (HAM) in colonic anastomosis in dogs. Materials and Methods Eight cross-breed male dogs were divided into two equal groups. After anesthesia and exploration, 5cm of left colon was resected, and end-to-end anastomosis was performed in a single layer. In the treatment group (B), HAM patch measuring 2×3 cm was wrapped around the anastomotic line. Mann-Whitney U test was used to compare the results in the two groups due to small sample size, and normal distribution of data was examined using the kolmogorov-simirnov test (P = 0.03). Results Modified scoring system for surgical wound healing was used to identify the grade of healing in all samples. The healing score was significantly higher in the HAM group (P = 0.01). Conclusions HAM plays a positive role in healing of colonic anastomosis, and would lead to better histological outcomes compared to simple anastomosis in dogs.